The influence of cisplatin dose variations during concurrent weekly chemo-radiation in stage IIB cervical cancer at Groote Schuur Hospital - Jemu, Mtabeni (Division of Radiation Oncology, 2018)
Objective: To examine the effect of treatment and tumour factors on the overall survival (OS) of patients completing chemo-radiation (CRT) for stage IIB cervical cancer. Materials and methods: Retrospective audit of 228 patients with stage IIB cervical cancer treated between 1995 and 2010, who received CRT with at least 45 Gy external beam radiation, two to four brachytherapy insertions, and one or more cycles of concurrent weekly cisplatin (40mg/m², capped at 60 mg/week). Results: Mean tumour size was 5.5cm, bilateral parametrial involvement in 40% of patients, lateral parametrial involvement in 50%, and vaginal spread in 43%. Mean total dose to Point A was 83 Gy (range 61-96) linear quadratic equivalent dose to 2 Gy/fraction. Mean overall treatment time (OTT) was 45 days. The average weekly haemoglobin (AWHB) during treatment was 11.6 g/dL (range 8.8-15.5). Blood transfusions before or during chemo-radiation were given in 33% of patients. Two thirds of patients completed five or six cycles of weekly cisplatin. Reasons for fewer than five cycles were: scheduling failure, neutropaenia, and/or renal impairment. No outcome differences were observed for Monday vs. Thursday cisplatin administration. The 5-year OS was 60%. Patients completing fewer than six cycles had a worse OS (55 vs. 76%, p=0.02). By multiple regression analysis for OS, only six cycles of cisplatin, squamous histology, and AWHB>10g/dL were significant. Conclusions: Maintaining HB>10 and administering six cycles of weekly cisplatin at the dose regimen used appear to be requirements for maximal benefit during CRT of stage IIB cervical cancer.